2007
DOI: 10.1016/j.nurt.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Brain Mapping as a Tool to Study Neurodegeneration

Abstract: Summary: Alzheimer's disease (AD) is the most common neurodegenerative disorder for those 65 years or older; it currently affects 4.5 million in the United States and is predicted to rise to 13.2 million by the year 2050. Neuroimaging and brain mapping techniques offer extraordinary power to understand AD, providing spatially detailed information on the extent and trajectory of the disease as it spreads in the living brain. Computational anatomy techniques, applied to large databases of brain MRI scans, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 98 publications
(121 reference statements)
0
40
0
Order By: Relevance
“…3). Hippocampal function critical to memory is exceptionally sensitive to aging (Kausler 1994;Apostolova and Thompson 2007). The MWM test is considered to test hippocampal function (Vorhees and Williams 2006).…”
Section: Brain Sizementioning
confidence: 99%
See 2 more Smart Citations
“…3). Hippocampal function critical to memory is exceptionally sensitive to aging (Kausler 1994;Apostolova and Thompson 2007). The MWM test is considered to test hippocampal function (Vorhees and Williams 2006).…”
Section: Brain Sizementioning
confidence: 99%
“…The MWM test is considered to test hippocampal function (Vorhees and Williams 2006). Neurodegeneration of the hippocampus is widely implicated in the loss of spatial memory (navigation skills), dementia, and AD (Foster 1999;Apostolova and Thompson 2007). In AD, the rate of hippocampal atrophy is 3.5-4%/year, exceeding the ∼1.6%/year loss observed in normal aging by nearly 3-fold (Jack et al 1998(Jack et al , 2000.…”
Section: Brain Sizementioning
confidence: 99%
See 1 more Smart Citation
“…4 Recently, the possibility of an early diagnosis of AD has brought attention to the importance of neuroimaging investigations in predementia patients. 5 Several studies using region-of-interest (ROI) and voxel-based analyses have reported reduced volumes in the hippocampus, parahippocampal gyrus, cingulate and other brain regions in patients with mild cognitive impairment (MCI) and AD. 2,[6][7][8] The spatial pattern of brain atrophy in MCI is complex and highly variable and does not always progress in a linear manner.…”
Section: Introductionmentioning
confidence: 99%
“…Brain mapping techniques [18] can be used to quantify changes, for example in voxel-based morphometry [19,20], and more involved approaches estimate diffeomorphic changes in local brain structure [21] or construct local surface models [22] from volumetric measurements. Texture analysis is an interesting alternative [23] that has received little attention so far.…”
Section: Introductionmentioning
confidence: 99%